Measuring stress signaling responses of stomata in isolated epidermis of graminaceous species - Shen, Lei; Sun, Peng; Bonnell, Verity C.; Edwards, Keith J.; Hetherington, Alistair M.; McAinsh, Martin R.; Roberts, Michael R. (Frontiers in Plant Science, 2015)
Our current understanding of guard cell signalling pathways is derived from studies in a small number of model species. The ability to study stomatal responses in isolated epidermis has been an important factor in elucidating the mechanisms by which the stomata of these species respond to environmental stresses. However, such approaches have rarely been applied to study guard cell signalling in the stomata of graminaceous species (including many of the world’s major crops), in which the guard cells have a markedly different morphology to those in other plants. Our understanding of guard cell signalling in these important species is therefore much more limited. Here, we describe a procedure for the isolation of abaxial epidermal peels from barley, wheat and Brachypodium distachyon. We show that isolated epidermis from these species contains viable guard cells that exhibit typical responses to abscisic acid (ABA) and CO2, as determined by measurements of stomatal apertures. We use the epidermal peel assay technique to investigate in more detail interactions between different environmental factors in barley guard cells, and demonstrate that stomatal closure in response to external CO2 is inhibited at higher temperatures, whilst sensitivity to ABA is enhanced at 30°C compared to 20°C and 40°C.